Outcome after Anterior Cervical Decompression and Fusion – A Nationwide FinSpine Register Study of Independent Predictors of Outcome at 12 Months after Surgery for Degenerative Cervical Spine - Klimko, Nikolai; Danner, Nils; Salo, Henri; Kotkansalo, Anna; Leinonen, Ville; Huttunen, Jukka (Lippincott Williams & Wilkins, 2025)
Study Design.
Longitudinal, nationwide register study
Objective.
To identify independent predictors of clinical outcomes at 12 months for patients undergoing primary anterior cervical discectomy and fusion (ACDF) for degenerative cervical spine disease (DCSD).
Summary of Background Data.
ACDF is an established surgical treatment for DCSD. Identifying factors that predict successful surgical outcomes can improve patient selection and inform decision-making.
Methods.
This study utilized data from the Finnish national spine register (FinSpine), covering all Finnish centers which perform ACDF surgery. Patients undergoing primary ACDF surgery for DCSD between June 2016 and February 2024 without prior cervical spine surgery were included (n=5,517). Patients were grouped based on the patient symptom status (“Improved” vs. “Indifferent or worse”) at 12 months post-surgery. Predictive factors were identified using classification tree analysis followed by binary logistic regression.
Results.
At 12 months, 76.8% (n=1799) of patients reported symptom improvement, while 23.2% (n=542) reported that symptoms were indifferent or worse. Loss to follow-up for the outcome variable was 57.6% at 12-months. The Following factors were associated with better outcomes: shorter preoperative pain duration (≤1 year, OR: 1.95, P<0.001), lower preoperative Neck Disability Index (NDI) scores (≤42, OR: 1.37, P=0.012), and non-smoking (OR: 1.37, P=0.030). The initial diagnosis also influenced outcomes: patients treated for herniated discs and nerve root stenosis were more likely to report improvement compared to those with central canal stenosis or myelopathy (P<0.001). Gender, age, BMI, working status, regular use of pain medication, perioperative complications, muscle weakness, levels fused and use of plate versus stand-alone cage were not independently predictive of outcomes.
Conclusion.
Shorter preoperative pain duration, lower NDI scores, and non-smoking status were significant predictors of good outcomes at 12 months after ACDF surgery for DCSD. These findings can help to guide preoperative patient counselling and enhance evidence-based decision making for treating DCSD.